Pengaruh Tingkat Partisipasi Angkatan Kerja, Upah Minimum dan Investasi Terhadap Kemiskinan di Indonesia - adela delviera, adela delviera; Amar, Syamsul (Universitas Negeri Padang, 2024)
This research aims to analyze the influence of labor force participation rates, minimum wages and investment on poverty. This research uses secondary data sourced from the Central Statistics Agency (BPS) with three independent variables, namely labor participation, wages and investment, with the attachment variable being poverty. This research uses panel data regression analysis using the random effect model method with a cross section of 34 provinces in Indonesia and the 2018-2022 time series. The results found that investment had a negative and significant effect on poverty levels in Indonesia. Meanwhile, labor participation has a positive and significant effect on poverty levels in Indonesia and the minimum wage has a negative and insignificant effect on poverty levels in Indonesia. This indicates that low education and skills cause the income received by workers to be unable to meet their basic needs, as well as inequality between regions causing the minimum wage to have no significant effect on reducing poverty in Indonesia. Therefore, the government must improve the quality of human resources and equal distribution of income. in alleviating poverty in Indonesia